"Désenchantée I left Turkey, désenchantée I have left Europe": emotions, genre and gender in Zeyneb Hanoum's A Turkish Woman's European Impressions (1913). Issue 4 (2nd October 2019) - Adam, Sibyl
ABSTRACT: Zeyneb Hanoum's A Turkish Woman's European Impressions (1913) contains the letters of Zeyneb Hanoum and her sister, sent to the British journalist Grace Ellison during their travels as exiles through Europe after fleeing Istanbul. Ellison was crucial to the publication of this genre-bending narrative, which circulated as harem literature and travel writing while also resembling life writing. Scholarship on the text has valued its portrayal of feminist transcultural friendship and although critics have noted its distinctive use of emotive language, there is yet to be an interrogation of how this use of emotions as tone, language and structure disrupts conventions of genre and the wider historical context of the text. In light of the recent turn to affect theory and the history of emotions, this article reassesses this text's feminist value, through its relationship to literary traditions of travel and emotive elements of orientalism as a technique of imperial domination.